Catching a CAPTCHA: the impact of variable input on the processing of emerging orthographic representations - Olga Solaja; María Fernández-López; Davide Crepaldi; Manuel Perea (Language and Cognition)
Variability inherent to handwriting has been suggested to help establish more robust letter representations than other methods (e.g., typing). The present study tests whether encoding letter strings from a novel alphabet becomes more resistant to distortion when trained with variable input. Over 5 days, participants learned an 11-character artificial alphabet in a variable handwritten format involving reading, listening and handwriting practice. Another set of 11 artificial characters served as a visual control. Before and after the training, participants completed a masked priming same–different matching task with the novel alphabet letters. The key manipulation was in the primes: the identity/unrelated primes could be presented in a printed or distorted format. Results showed identity priming in both conditions, with a stronger effect for the printed primes. These effects increased post training for experimental and visual control scripts, indicating that exposure to variable input enhances distortion resistance even without explicit training. A second experiment assessed the transposed-letter effect – another marker of orthographic processing – in the novel scripts with an unprimed same–different matching task. Results showed that the transposed-letter effect occurred similarly before and after the training for both scripts. Therefore, letter shape variability when learning to read does not seem to boost orthographic processing.